The Influence of Customer Experience and Brand Image on Repurchase Intention Through Product Quality as a Moderator on the Zalora E-commerce Platform : A Conceptual Framework - Fatizah Amanda; Arry Widodo; Nurafni Rubiyanti; Anita Silvianita (Formosa Journal of Multidisciplinary Research, 2024)
The growth of the fashion e-commerce industry in Indonesia continues to increase rapidly. This is triggered by the increasing use of the internet and smartphones. Zalora, as a leading fashion e-commerce platform, has successfully become a prominent market in Indonesia by providing a wide range of fashion products from local and international brands. In this digital era, there has been a significant transition in consumer behavior and people are moving to do their shopping through online platforms, especially for fashion products. This study aims to examine the impact of customer experience and brand image on repurchase intentions through product quality as a regulator on the Zalora e-commerce platform. This study was conducted using a quantitative approach. Data was collected through questionnaires and analyzed using the regression method. The purpose of this research is to contribute to further understanding of the influence of customer experience and brand image on customer repurchase intentions on the Zalora e-commerce platform. In addition, this study also aims to determine how product quality affects the relationship between customer experience and brand image with the intention to repurchase.